2011
DOI: 10.1111/j.1943-278x.2011.00042.x
|View full text |Cite
|
Sign up to set email alerts
|

Risk of Suicidal Ideation in Adolescents with both Self‐Asphyxial Risk‐Taking Behavior and Non‐Suicidal Self‐Injury

Abstract: This study examined adolescent participation in self-asphyxial risk-taking behaviors (SAB), sometimes known as the "choking game," and its relationship with other adolescent risk behaviors, including non-suicidal self-injury (NSSI). Researchers proposed that participation in SAB and NSSI would be associated with suicidal behavior, disordered eating, and substance use. Using a large community-based sample, results revealed preliminary associations between SAB and other risk-taking behaviors. Adolescents who had… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
28
1
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(33 citation statements)
references
References 24 publications
3
28
1
1
Order By: Relevance
“…Similar proportions have been reported in other studies both in Canada (Nixon, Cloutier, & Aggarwal, 2002;Nixon, Cloutier, & Jansson, 2008) and elsewhere (see, e.g., Brausch & Gutierrez, 2010;Madge, Hewitt, Hawton et al, 2008;Muehlenkamp & Gutierrez, 2007). Brausch, Decker, & Hadley (2011) found 21% of their adolescent sample engaged in NSSI in the last 12 months. Other studies on NSSI have reported higher prevalence rates of this behavior than that found in the present study (see, e.g., Cloutier, Martin, Kennedy et al, 2010;Heath, Toste, Nedecheva et al, 2008).…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…Similar proportions have been reported in other studies both in Canada (Nixon, Cloutier, & Aggarwal, 2002;Nixon, Cloutier, & Jansson, 2008) and elsewhere (see, e.g., Brausch & Gutierrez, 2010;Madge, Hewitt, Hawton et al, 2008;Muehlenkamp & Gutierrez, 2007). Brausch, Decker, & Hadley (2011) found 21% of their adolescent sample engaged in NSSI in the last 12 months. Other studies on NSSI have reported higher prevalence rates of this behavior than that found in the present study (see, e.g., Cloutier, Martin, Kennedy et al, 2010;Heath, Toste, Nedecheva et al, 2008).…”
Section: Discussionsupporting
confidence: 81%
“…For example, Brausch, Decker, and Hadley (2011) found that adolescents who use substances (alcohol, tobacco, and other drugs) were more likely to have engaged in both NSSI and self-asphyxial risk-taking behaviors. Giletta, Scholte, Engels et al (2012) also analysed data from Italy, United States and the Netherlands and found cigarette smoking and frequent marijuana use to be more strongly related to NSSI in the sample from the United States than the samples from Italy and the Netherlands.…”
Section: Introductionmentioning
confidence: 97%
“…Brausch and colleagues, through a health behavior screening made in rural region, discovered that as many as 17% of adolescents had practiced a Self-Asphyxial risk-taking behavior, and that adolescents who reported SAB also reported more suicide ideation and attempts than those who had not. 30 Adolescents who had engaged both SAB and NSSI (non suicidal self-injury) would have a great chance to make other risk behaviors, including suicide. Otherwise, Andrew and Fallon reported that these adolescents usually are athletic and like to extreme everything and they think that this activity is safe just because alcohol or drugs are not involved.…”
Section: The Choking Gamementioning
confidence: 99%
“…One of the underlying purposes was to confirm the contribution of substance use and risk-taking behaviors as strong predictors of CG participation. [16][17][18][19] Nonetheless, our main goal for this research was to identify additional predictors of this dangerous activity, which is crucial for designing adequate preventive interventions.…”
mentioning
confidence: 99%